Waste Rubber Tyre As Road Divider Application - Zarith Sufiah , Mustafa (2010)
Waste tyre is performed as a main material for produced a valuable product. Commonly, land filling of waste tyres for disposal purpose is relatively cheap and easy to achieve, but in reality, this is a waste are potentially to produce a valuable raw materials and leads to many other problems if rubber are not enough for customer demand. This research is purposed to utilize a waste tyre as an impact for road divider and waste tyre are crushed for melted to develop a shape of rubber sheet. The simulate rubber sheet is laminated towards the plate of Galvanized Iron and Galvanized Steel. From the test analysis on the rubber road divider, the tensile test were giving values of tensile strength, tensile strain and young's modulus of waste rubber tyre after it melted. One piece of rubber layer (3mm) able to absorb ± 30 % while absorption would be increased as ± 40 % from two piece layer (6mm) from the impact test. Rubber acted as toughening agent which prolonged the deformation capabilities of the fabricated samples test.